Influence of the Frequency of Speech Therapy on the Velopharyngeal Gap in Cleft Lip and Palate Patients After Primary Palatoplasty - Jaruvattanadilok, Supitchaya; Kasirawat, Chayada; Ko-iam, Wasana; Sonsuwan, Nuntigar; Khwangern, Krit (Biomedical Sciences and Clinical Medicine, 2026)
Objective The craniofacial conditions of cleft lip and cleft palate (CLP) have been found to be common worldwide, especially in Asia and Thailand. Nevertheless, there are few studies of the association between the frequency of speech therapy and the impact on the velopharyngeal (VP) gap and speech outcome. This study aimed to evaluate the association between the frequency of speech therapy and the VP gap after primary palatoplasty. Methods This retrospective cohort study collected data on 95 patients with CLP or isolated cleft palate who underwent primary palatoplasty at Maharaj Nakorn Chiang Mai Hospital between 2006 and 2018. Log risk regression analysis was carried out to identify the effect of frequency of speech therapy in reducing the VP gap including relative risk (RR) and 95% confidence interval (95%CI). Results From univariable analysis, influence of speech therapy frequency on the presence of a VP gap showed a crude RR = 0.70 (95%CI = 0.49-0.98). Additionally, the frequency of speech therapy in the multivariable analysis showed an adjusted RR = 0.74, 95%CI = 0.46-1.19. The associated anomalies and syndromes showed a statistically significant correlation with a VP gap (adjusted RR = 1.60, 95%CI = 1.12-2.28). Conclusion Patients who receive speech therapy 5-10 times or more showed a decrease in the incidence of a VP gap of at least 26%; however, this did not reach statistical significance. Nevertheless, it is recommended that speech therapy with cleft lip and cleft palate patients should be continued for at least 5 to 10 sessions.